SUCCESS OF PREGNANCY AND CHILDBIRTH IN SYNDROME HERLYN-WERNER-WUNDERLICH (HWW)/ SYNDROME OHVIRA: LAPORAN KASUS LANGKA - Patricia Riwiris Sry Rezeki Samosir; Dhaniel Theolia Persadanta Ginting; Kevin Nicholas Rumahorbo; Edwin Martin Asroel (Yayasan Nuraini Ibrahim Mandiri, 2026)
Herlyn-Werner-Wunderlich (HWW) syndrome also known as OHVIRA (Obstructed HemiVagina and Ipsilateral Renal Agenesis) syndrome is a rare form of Müllerian Duct Anomalies (MDA). Uterine malformations may be associated with adverse obstetric outcomes, including increased rates of miscarriage, malpresentation, and preterm birth. Case Illustration: A 29-year-old woman at 36-37 weeks' gestation was diagnosed with Premature Rupture of Membranes with OHVIRA syndrome. The patient underwent a cesarean section under spinal anesthesia. A baby girl was born with a birth weight of 2980 grams and an Apgar score of 8/9. The uterus appeared didelphysic. Discussion: This case study examines a nulliparous woman with premature rupture of membranes (PROM) and OHVIRA syndrome. Delivery was assisted by cesarean section. Conclusion: OHVIRA syndrome is a rare condition that carries many risks in pregnancy. However, there have been several cases of successful pregnancies and deliveries. Suggestion: A multidisciplinary approach and patient education are needed to increase the success of pregnancy and childbirth.